1997
DOI: 10.1111/j.1440-6055.1997.tb01451.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Moisture on Oviposition by Childers Canegrub, Antitrogus parvulus Britton (Coleoptera: Scarabaeidae)

Abstract: Ovipositing Childers beetles, Antitrogusparvulus Britton, exhibit preference for soils of certain moisture levels. In a choice trial, A . parvulus laid most eggs in soil at approximately -74 kPa (near field capacity), no or very few eggs in soil near wilting point or drier, and few eggs in soil above field capacity (approximately -5.7 kPa). Under no-choice conditions most females retained their eggs if soil was near wilting point, oviposited immediately in soil near field capacity, and tended to extend egg-lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 7 publications
1
13
1
Order By: Relevance
“…These results indicate that if females do migrate between soil patches, they fly to the nearest available soil patch (3.5–23 km, Table 3) and that genetic variation between favourable patches of soil could be due to reproductive isolation between favourable habitats. Our work supports previous observations that suggest that the females of A. parvulus are philopatric, irrespective of the distribution of soil types (Mungomery 1932; Britton 1986; Logan 1997a). Hence, the coalescence of COII to monophyly for each region (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results indicate that if females do migrate between soil patches, they fly to the nearest available soil patch (3.5–23 km, Table 3) and that genetic variation between favourable patches of soil could be due to reproductive isolation between favourable habitats. Our work supports previous observations that suggest that the females of A. parvulus are philopatric, irrespective of the distribution of soil types (Mungomery 1932; Britton 1986; Logan 1997a). Hence, the coalescence of COII to monophyly for each region (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…2002a). Logan (1997a) showed that A. parvulus exhibited preference for soils with moisture contents of approximately −74 kPa (near field capacity) and, if soil conditions are unsuitable, females will retain their eggs until further rain or irrigation improves soil‐moisture conditions. This suggests that on a broader scale heterogeneous soil moisture conditions due to differences in topography, plant cover, rainfall intensity and irrigation will probably lead to variability in egg‐laying by A. parvulus and in this way oviposition might contribute to patchy larval distributions (Logan 1997a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain levels of moisture in the soil were found essential for survival and hatching of eggs and also for the survival of the grubs especially in their first instars (Potter and Gordon, 1984). Logan (1997) reported that childers canegrub, Antitrogus parvulus laid most eggs in soil near field capacity, no or very few eggs in soil near wilting point and few eggs in soil above field capacity. Tai Hsien (1965) found that soil moisture at 20-30 per cent field capacity was optimum for egg survival.…”
Section: Grub Density In Different Habitatsmentioning
confidence: 99%